Survey of the UK veterinary profession 2: sources of information used by veterinarians - Nielsen, T.D.; Dean, Rachel S.; Massey, A.; Brennan, Marnie L. (BMJ Publishing Group, 2015)
Access to the most up-to-date evidence is an important cornerstone for veterinarians attempting to practice in an evidence-based manner; therefore, an understanding of what and how information is accessed is vital. The aim of this study was to identify what resources the UK veterinary profession access and regard as most useful. Based on questionnaires received from veterinarians, the Veterinary Times was nominated as most often read journal or magazine by respondents (n=3572, 79 per cent). In Practice (n=3224, 82 per cent) and the Veterinary Record (n=165, 34 per cent) were seen as most useful by clinicians, and non-clinicians, respectively. Google was the most often nominated electronic resource by all respondents (n=3076, 71 per cent), with Google (n=459, 23 per cent) and PubMed (n=60, 17 per cent) seen as most useful by clinicians and non-clinicians, respectively. The abstract and conclusion sections were the most read parts of scientific manuscripts nominated by all respondents. When looking for assistance with difficult cases, colleagues were the common information choice for clinicians. Different sections of the veterinary profession access information, and deem resources useful, in different ways. Access to good quality evidence is important for the practice of evidence-based veterinary medicine, and therefore, researchers should think about disseminating their findings in a targeted way for optimal use by the profession.